2012
DOI: 10.1007/s10162-012-0337-0
|View full text |Cite
|
Sign up to set email alerts
|

Over Half the Hair Cells in the Mouse Utricle First Appear After Birth, with Significant Numbers Originating from Early Postnatal Mitotic Production in Peripheral and Striolar Growth Zones

Abstract: Many non-mammalian vertebrates produce hair cells throughout life and recover from hearing and balance deficits through regeneration. In contrast, embryonic production of hair cells declines sharply in mammals where deficits from hair cell losses are typically permanent. Hair cell density estimates recently suggested that the vestibular organs of mice continue to add hair cells after birth, so we undertook comprehensive counting in murine utricles at different ages. The counts show that 51 % of the hair cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
127
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(144 citation statements)
references
References 58 publications
17
127
0
Order By: Relevance
“…By culturing the organs in medium supplemented with 5-ethynyl-2′-deoxyuridine (EdU), we labeled the proliferating cells at each stage. In accord with previous results (14), we observed proliferating cells at the periphery of the utricular macula and in the striola, the organ's central region (Fig. S1 A-C).…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…By culturing the organs in medium supplemented with 5-ethynyl-2′-deoxyuridine (EdU), we labeled the proliferating cells at each stage. In accord with previous results (14), we observed proliferating cells at the periphery of the utricular macula and in the striola, the organ's central region (Fig. S1 A-C).…”
Section: Resultssupporting
confidence: 81%
“…To ascertain whether the morphological abnormalities of the vestibular organs in the SoxC CKO mice arose from deficiencies in supporting cell proliferation, we labeled proliferating cells with EdU and analyzed the inner ears of E18.5 embryos. As shown previously (14), a band of proliferating supporting cells occurred along the convex abneural periphery of a WT utricle (Fig. 4E).…”
Section: Significancementioning
confidence: 62%
See 1 more Smart Citation
“…Notably, hair cells of the adult cochlea in mammals do not usually regenerate. Vestibular hair cells have been known to regenerate when injured [Warchol et al, 1993;Yamane et al, 1995], and others have found that half of the hair cells in the mouse utricle first appear after birth, but that they only appear 2 weeks after birth [Burns et al, 2012]. However, regeneration of inner ear cells is not typical.…”
Section: Mirna Expression Of the Mouse Inner Ear During Agingmentioning
confidence: 99%
“…Neurogenesis and the production of sensory patches continue together for several days until neurogenesis is extinguished (Raft, et al, 2007). However, sensory tissue continues to differentiate for days and sometimes weeks: for instance, the mouse utricular macula does not finish adding hair cells until two weeks after birth (Burns, et al, 2012). …”
Section: Introductionmentioning
confidence: 99%